The factors affecting the decision making process of interior design graduates in choosing a career path - Poyaoan, Kristel Anne B.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT The interior design industry has been undergoing globalization as it created diverse career paths for interior design graduates. The main objective of this study was to analyze the trends of the influence of the factors from previous studies that affect the decision of interior design graduates in choosing a career path. This study also aims to determine the extent of influence of the three identified present issues such as gender issues, Philippine Interior Design Act of 2012, and ASEAN Integration on the decision of interior design graduates in choosing a career path. Multiple research design utilizing quantitative and qualitative research methods was used for this study. The 56 respondents for this study, acquired from a snowball sampling design, were composed of interior design graduates who have current jobs, reside in the Philippines, graduated from schools offering interior design degree in the Philippines, had either taken the board exam or not, and had either passed the board exam or not. An online survey and a more personal and in-depth interview was used to reach the objective of this study. Interior design graduates still consider interior design education, need of salary or income, and licensure board examination in choosing a career path while personal issue is just considered by a few. The career development and enhancement is now considered by interior design graduates as a factor affecting their career path. The Philippine Interior Design Act of 2012 has the greatest influence among the three present issues identified by the researcher. It is followed by the ASEAN Integration which brings diverse career opportunities as well as foreign competition to Filipino professionals. The gender issues have no affect on the majority of interior design graduates and it, together with the need of salary or income, produced an emerging factor such as age.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Interior decoration -- Vocational guidance